Pengaruh Motivasi Spiritual, Manajemen Waktu dan Kewirausahaan terhadap Kemandirian Ekonomi Berbasis Santripreneurship - Siti Khumairoh; Adhi Pradiptya; Asih Niati (GREAT: Jurnal Manajemen dan Bisnis Islam, 2026)
This research aim to determine and analyze influence  spiritual motivation, management time and entrepreneurship on independence economy based santripreneurship (study at the LP3iA Narukan Islamic Boarding School). Type research used is method study quantitative with use tool data processing in the form of SPSS version 26.Research use variables bound that is independence economy and 3 variables free that is spiritual motivation , management time And entrepreneurship . Data in study This in the form of primary data with 34 respondents as sample of the 55 populations which are students active in the entrepreneurship unit Islamic boarding school . Retrieval sample use non-probability sampling technique with purposive sampling technique.Previously research related the same variable there is gap, then need done study update. Results study This show that spiritual motivation And entrepreneurship own influence positive And significant to independence economy. Meanwhile management time own influence positive However No significant to independence economy.